Preserving Heritage and the Values of Exchange: Lessons from Nigeria. Issue 12 (December 2013) - Probst, Peter
Abstract Research on heritage preservation in Africa shows a field shaped by different and often opposite positions as to the actual meaning of heritage. Does heritage signify valuable remnants of the past that require safeguarding and protection? Or, is heritage first and foremost a contemporary practice by which the past comes to matter in the present? This paper aims to link and negotiate between these two positions. The empirical basis stems from my own research on how the sacred grove of the Yoruba river deity Osun in Southwest Nigeria became a UNESCO World Heritage Site. Drawing on the insights of this research, I argue that heritage is a relationship embedded in spheres of exchange that generate both moral and material forms of value. Conceiving heritage as exchange, so I contend, not only allows for a better understanding of the multiple values of heritage; it also sharpens interest in the struggles of control over the media of exchange. This paper examines these struggles with respect to the different spheres of exchange (local, national, and global) in which the grove of the river goddess Osun is entangled.